Dynamical behavior and control strategy of a dengue epidemic model - Bocanegra Villegas, Laura Valentina; Sánchez Ramírez, Cuauhtémoc; Usaquén Perilla, Sandra (Cultura Científica y Tecnológica, 2024)
Mosquitoes of the species Aedes (Ae. aegypti or Ae. albopictus) can transmit Dengue, Chikungunya, Zika, and Yellow Fever. Of the people's mobility and increasing population density, diseases such as Dengue have been an epidemic in recent years, becoming a globally important health problem. Those responsible for creating vector control campaigns and medical staff are interested in identifying tools to predict the seasonal peak of the dengue outbreak and identify related climate factors that contribute to the increase in the number of mosquitoes. The purpose of this research is to simulate the behavior of the mosquito population with system dynamics. For simulation, the main variables entered are precipitation, temperature, and epidemiological week. The model is the first phase of a project that aims to provide a tool for simulating outbreaks of dengue with system dynamics, a basis for predicting the spread of the dengue.